Packaging materials with desired mechanical and barrier properties and full chemical recyclability - Ainara Sangroniz (Nature Portfolio, 2019)
Biodegradable plastics usually have poorer mechanical or transport properties compared to conventional plastics. Here the authors show a class of biorenewable and chemically recyclable plastics based on copolymers of γ-butyrolactone and its ring-fused derivative, with competitive properties compared to conventional plastics.